Anomaly "Marriage Mut'ah" in Arab Village Bogor - Safira Amalia Nuranisa; Nunung Nurwati; Muhammad Fedryansyah (LEGAL BRIEF, 2022)
This article focuses on the problem of deviant behavior that examines the phenomenon of tourist irregularities labeled halal. The focus of the situation in this study is to explain the phenomenon of marriage mut'ah (contract marriage) currently as halal tourism in the Arab village of Cisarua in Bogor Regency. This study uses a qualitative approach to develop concepts, explain the reality associated with a theory, and develop an understanding of a phenomenon. The results of studies show that the phenomenon of contract marriage is a social-cultural formation, a social construction, not an instinct, so contract marriage can be interpreted as a form of efforts to legalize the form of adultery, adultery, struggles to escape from the pressures of poverty, efforts to legitimize sexual desire so as not to say cheating, all of which are very dependent on their society. The practice of contract marriages is done through brokers or specific individuals whose place is hidden where the whereabouts are unknown. It can be concluded that the current control over the phenomenon of marital mut'ah is considered to be no longer sufficient if it is only based on the family. Therefore, social control must involve various parties; it is no longer sufficiently preventive or persuasive. On the other hand, simultaneously by multiple groups, whether preventive or repressive, non-violence (transparent) or coercive is still carried out in various forms.